Adsorption of diclofenac, sulfamethoxazole and levofloxacin with powdered activated carbon - Lember, Erki; Pachel, Karin; Loigu, Enn (International Conference “Environmental Engineering”, 2017)
The presence of pharmaceutical residues in the receiving waterbodies of wastewater treatment plants (WWTP) and in the environment has become a global concern. We can now say for certain that, having metabolised in our bodies, partially modified or unmodified pharmaceuticals will reach WWTP. However, WWTP are not designed for the removal of such com pounds. Only a small fraction of pharmaceuticals decompose during biological treatment or are adsorbed in sediment. There fore, it is essential to find a treatment process that is capable of removing pharmaceutical residues. The aim of the present study was to research the removal of three pharmaceuticals found in the environment, namely diclofenac (DCF), sulfamethoxazole (SMX) and levofloxacin (LFX), through the use of powdered activated carbon (PAC). To this end, adsorption tests were con ducted where the adsorption capacity was estimated according to the adsorbent dose and the residence time of the process. LFX had the highest adsorption rate: the removal effectiveness was 77% in a residence time of 5 minutes and in 60 minutes a stable indicator was achieved whereby 94% of LFX had become adsorbed. The worst adsorption property was observed for SMX, as 68% of SMX was adsorbed in a residence time of 60 minutes. According to the conducted tests, the Freundlich adsorption isotherms and constants characterising the adsorption were found where the DCF K was 23.8, the SMX K was 34.3 and the LFX K was 106.1. This test demonstrated that the pharmaceuticals selected for the experiment could easily be subjected to adsorption processes and could be removed by means of PAC.
Keywords: adsorption of pharmaceuticals; removal of pharmaceutical residues; diclofenac removal; sulfamethoxazole removal